Pemetaan Kata Kunci dan Kolaborasi Penulis dalam Penelitian Financial Disclosure: Studi Bibliometrik - Judijanto, Loso (Eastasouth Institute, 2025)
This study aims to map the development of research on financial disclosure through a bibliometric approach. The research data were obtained from the Scopus database and analyzed using VOSviewer software to identify publication trends, author collaborations, inter-country relations, and the intellectual structure in this field. The analysis reveals that financial disclosure has become a central theme frequently associated with related topics such as corporate governance, non-financial disclosure, corporate social responsibility, and firm performance. In terms of authorship, several prominent scholars were identified as making significant contributions and forming closely connected research collaboration clusters. Geographically, the United States, the United Kingdom, and European countries dominate both publication output and international collaboration networks, while Asian countries have begun to show increasing contributions over the last decade. These findings not only highlight the knowledge structure and the developmental direction of financial disclosure research but also provide important implications for the advancement of theory, policy, and accounting practices in the era of transparency and sustainability.